Kepercayaan Pelanggan dan Citra Perusahaan Dalam Meningkatkan Loyalitas Pelanggan - Surip, Surip (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2023)
Customer trust and company image are the main factors that can increase customer loyalty.  To determine the effect of customer trust and company image on customer loyalty is the purpose of this study.  This research data is a customer of the warehousing department of PT Agung Raya with a population of 300 customers. The sampling technique in this study used a sample size web.raosoft.com with an error rate of 10% so that a sample of 75 respondents was obtained. Disseminating questionnaires is a method of data collection. This research uses multiple linear regression analysis as its analysis method. The results showed that customer trust and company image positively affected customer loyalty, and the effect was 76.8% while 23.2% was influenced by other variables. The variable that has a dominant influence is the company's image, with an influence of 68.7%. The contribution of this study is to expand marketing management literature related to customer trust and corporate image in the context of organizations.